Combined Application of Potassium and Zinc Improves Water Relations, Stay Green, Irrigation Water Use Efficiency, and Grain Quality of Maize under Drought Stress. (26th August 2020) - Hussain, Sajid; Maqsood, Muhammad; Ijaz, Muhammad; Ul-Allah, Sami; Sattar, Abdul; Sher, Ahmad; Nawaz, Ahmad
Abstract: Maize ( Zea mays L.) plays an important role in the global food security, but its production is threatened by climate change, especially drought stress. Potassium (K) and zinc (Zn) are considered useful to mitigate the negative consequences of drought stress in plants. Therefore, the objective of this two-year study was to identify the best combination of K and Zn application to improve the water relations, photosynthetic pigments, yield, irrigation water use efficiency (IWUE) and grain quality of maize sown under mild and severe drought stress conditions. The consisted of three drought stress levels viz. 1) well-watered as control (WW), 2) mild drought (MD) with 25 mm of potential soil moisture deficit (PSMD), 3) severe drought (SD) with 50 mm of PSMD and six K-Zn treatments: i.e. 125, 100 and 150 kg ha −1 K with 0 and 12 kg ha −1 Zn. The results indicated that K-Zn application improved the water relations and chlorophyll contents, biological yield and grain quality, irrespective of water stress treatment. The combined application of K-Zn under mild drought stress produced statistically same biological yield and grain quality as under well-irrigated without K-Zn fertilization and also produced compratively higher IWUE, biological yield and grain quality under sverer drought stress. Hence, the application of K at 150 kg ha −1 in combination with Zn at 12 kg ha −1 might be useful to improve the maize production and grain quality under drought stress. As IWUE was low in WW conditions, therefore, irrigation scheduling must be re-evaluated for optimum water use efficiency.